Mechanical Properties of High-Strength High-Performance Reinforced Concrete Shaft Lining Structures in Deep Freezing Wells - Shilong Peng; Chuanxin Rong; Hua Cheng; Xiaojian Wang; Mingjing Li; Bin Tang; Xuemei Li (Advances in Civil Engineering)
As coal resources must be mined from ever deeper seams, high-strength, high-performance concrete shaft linings are required to resist the load of the soil surrounding the deep freezing well. In order to determine the optimal concrete mix for the unique conditions experienced by such high-strength high-performance reinforced concrete shaft lining (HSHPRCSL) structures in deep freezing wells, an experimental evaluation of scaled HSHPRCSL models was conducted using hydraulic pressure load tests. It was observed that as the specimens ruptured, plastic bending of the circumferential reinforcement occurred along the failure surface, generated by compression-shear failure. These tests determined that HSHPRCSL capacity was most affected by the ultimate concrete uniaxial compressive strength and the thickness-diameter ratio and least affected by the reinforcement ratio. The experimental results were then used to derive fitting equations, which were compared with the results of theoretical expressions derived using the three-parameter strength criterion for the ultimate bearing capacity, stress, radius, and load in the elastic and plastic zones. The proposed theoretical equations yielded results within 8% of the experimentally fitted results. Finally, the finite element analysis method is used to verify the abovementioned results, and all errors are less than 12%, demonstrating reliability for use as a theoretical design basis for deep HSHPRCSL structures.